Like Islam Project, Strategi Dakwah Masa Kini - Syahida Yasya Moeniri (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
Islam is the religion with aesthetics. It is Muslim’s obligation to generously spread the beauty of Islamic teachings in all aspects of life, health, education and economy. For that reason, Like Islam Project tries to promote da’wah Islam through its business, a creative home industry. Like Islam Project uses Islamic quotes in their merchandise products to convey Islamic teachings. This study is a qualitative descriptive study. Data is collected through face-to-face interview with the owner and an online interview, using Whatsappplatform, with 2 of their resellers. To validate observation and documentation are performed. Result shows that Like Islam Project has special strategies to reach their goals. Those strategies are clear intention, qualified human resources, setting da’wah targets, selecting appropriate media, and also having original idea and concept. Background and da’wah style of Like Islam Project are also discussed.